Machine vision : theory, algorithms, practicalities - Davies, E. Roy, 1948- (Amsterdam : Elsevier, 2005)
In the last 40 years, machine vision has evolved into a mature field embracing a wide range of applications including surveillance, automated inspection, robot assembly, vehicle guidance, traffic monitoring and control, signature verification, biometric measurement, and analysis of remotely sensed images. While researchers and industry specialists continue to document their work in this area, it has become increasingly difficult for professionals and graduate students to understand the essential theory and practicalities well enough to design their own algorithms and systems. This book directly addresses this need.
Keywords: Beeldverwerking; Computer algorithms; Computer vision